CD147-specific chimeric antigen receptor T cells effectively inhibit T cell acute lymphoblastic leukemia. (28th August 2022) - Zheng, Nai-Shan; Zhao, Xiang-Yu; Wei, Ding; Miao, Jin-Lin; Liu, Ze-Kun; Yong, Yu-Le; Zhang, Ren-Yu; Guo, Yi-Xiao; He, Lin; Wang, Bin; Sun, Xiu-Xuan; Yang, Hai-Jiao; et al.
Abstract: T cell acute lymphoblastic leukemia (T-ALL) is invasive and heterogeneous, and existing therapies are sometimes unsuccessful. Chimeric antigen receptor (CAR) T cell therapy is a breakthrough tumor treatment method, particularly for B cell acute lymphoblastic leukemia. We found that CD147 was highly expressed in tumor T cells of T-ALL patients and T cell lymphoma. Therefore, CD147-CAR T cells that contain a humanized single-chain variable fragment targeting human CD147 and a second-generation CAR frame were constructed for treating T-ALL. CD147-CAR T cells were able to maintain a healthy proliferation rate, preserving a subset of CD62L+/CCR7+ memory T cells. CD147-CAR T cells showed a potent anti-tumor activity against human T-ALL cell line and T-ALL blasts, releasing high level of cytokines in the process. However, CD147-CAR T cells exhibited potential safety toward human normal cells and CD147-deficent cells . NOD/ShiLtJGpt- Prkdc em26Cd52 Il2rg em26Cd22 /Gpt mice were used to establish a T-ALL xenograft model and CD147-CAR T cells conferred robust protection against T-ALL progression and significantly improved survival in mice. Overall, we found that CD147 is a potential antigen target of CAR T cell therapy for T-ALL. Highlights: Construction of CD147-specific chimeric antigen receptor (CD147-CAR) T cells. Construction of T-cell acute lymphoblastic leukemia (T-ALL) xenograft model. CD147-CAR T cells exhibit an anti-tumor activity on T-ALL in vitro and in vivo . CD147 is a potential antigen target of CAR T cell therapy to treat T-ALL.